Implementation of Telegram Chatbot as an Effective Communication Means at SMK PGRI 1 Tangerang - Didi Kurnaedi; Agus Danu Widodo (bit-Tech, 2023)
The use of technology in education continues to grow in response to demands for efficiency and effectiveness of communication in the school environment. This research aims to investigate the application of Telegram chatbots as an effective means of communication at SMK PGRI 1 Tangerang. The research method used is descriptive qualitative, focusing on collecting data through observation, interviews and content analysis of the use of Telegram chatbots among students, teachers and school administration staff. The research results show that the application of the Telegram chatbot as a means of communication has made a significant contribution to increasing interaction and access to information in the educational environment of SMK PGRI 1 Tangerang. Students, teachers and administrative staff showed a positive response to the use of Telegram chatbots as an efficient communication alternative, facilitating the exchange of information regarding schedules, assignments and other important information. Qualitative findings support the idea that Telegram chatbots have become an effective means of communication at SMK PGRI 1 Tangerang, opening up new opportunities for more dynamic interactions and easier accessibility of information among the school community. The implications of these findings indicate that the integration of communication technology such as the Telegram chatbot can be an innovation that has the potential to change the communication paradigm in the educational environment.